العوامل المؤثرة علي مدى استخدام نظام التأجير التمويلي بالمصارف التجارية "دراسة ميدانية علي المصارف التجارية الليبية العاملة في المنطقة الشرقية " (Economic studies journal, 2019)
The study aimed to identify the factors affecting the extent of using financial leasing technique in Libyan commercial banks working in the Eastern region , moreover to show the benefits will the Libyan commercial banks obtain resulting of using the financial leasing technique. In order to achieve the objectives of the study the questionnaire was designed according to previous studies and distributed to the employees of the Libyan commercial banks, it has distributed to (48) employees after that (38) returned which they were usable of analysis mainly (66%).The most important findings was that financing leasing technique is not applied to Libyan commercial banks although there is law regulating the use of this technique, and the banks have qualified staff correctly apply the financial leasing technique, furthermore the study concluded that there is a relationship and effect of the selected five factors and using financial leasing in Libyan bank.According to findings, the study made some recommendations such the banks need to support the awareness of financing leasing technique among staff of banks, in addition training to deal with financing leasing technique is necessary to provide the Libyan banks positive impact in the development of funding for economic projects.
Keywords: Leasing financial; Libyan commercial banks